Nab-paclitaxel improves disease-free survival in early breast cancer: GBG 69–Geparsepto - Untch, Michael; Jackisch, Christian; Schneeweiss, Andreas; Schmatloch, Sabine; Aktas, Bahriye; Denkert, Carsten; Schem, Christian; Wiebringhaus, Hermann; Kümmel, Sherko; Warm, Mathias; Fasching, Peter; Just, Marianne; et al. (Journal of Clinical Oncology, 2019)
PURPOSE The GeparSepto trial demonstrated that weekly nanoparticle albumin-bound (NAB)–paclitaxel significantly improves the pathologic complete remission rate compared with weekly solvent-based (sb) paclitaxel followed by epirubicin plus cyclophosphamide as neoadjuvant treatment in patients with primary breast cancer (BC). Here, we report data on long-term outcomes. METHODS Patients with histologically confirmed primary BC were randomly assigned in a 1:1 ratio to 12 times weekly NAB-paclitaxel 150 mg/m2 (after study amendment, 125 mg/m2) or weekly sb-paclitaxel 80 mg/m2 followed in both arms by four times epirubicin 90 mg/m2 plus cyclophosphamide 600 mg/m2 every 3 weeks. Patients with human epidermal growth factor receptor 2 (HER2)-positive BC received dual antibody treatment with trastuzumab (8 mg/kg loading dose followed by 6 mg/kg every 3 weeks) and pertuzumab (840 mg loading dose followed by 420 mg every 3 weeks) concurrently to chemotherapy and continued for 1 year. RESULTS A total of 1,206 patients started treatment, 606 with NAB-paclitaxel and 600 with sb-paclitaxel. After a median follow-up of 49.6 months (range, 0.5 to 64.0 months), 243 invasive disease–free survival (iDFS) events were reported (143 in the sb-paclitaxel and 100 in the NAB-paclitaxel arm). At 4 years, overall patients treated with NAB-paclitaxel had a significantly better iDFS compared with sb-paclitaxel (84.0% v 76.3%; hazard ratio, 0.66; 95% CI, 0.51 to 0.86; P = .002), whereas overall survival did not significantly differ between the two treatment arms (89.7% v 87.2%, respectively; hazard ratio, 0.82; 95% CI, 0.59 to 1.16; P = .260). Long-term follow-up of the treatment-related peripheral sensory neuropathy (PSN) showed a significant decrease of the median time to resolve PSN after NAB-paclitaxel 125 mg/m2 compared with NAB-paclitaxel 150 mg/m2. CONCLUSION The significantly higher pathologic complete response rate with NAB-paclitaxel translated into a significantly improved iDFS in patients with early BC as compared with sb-paclitaxel. PSN improved much faster under NAB-paclitaxel 125 mg/m2 compared with NAB-paclitaxel 150 mg/m2.
CRIS-Team Scopus Importer:2019-09-03